Land use and morphometric evolution of valleys in the municipality of Daloa (Central-western Côte d’Ivoire) - KOUAO, N'kpomé Styvince Romaric (Geografares, 2025)
The morphometric evolution of the valleys and the associated geomorphological risks in the major Ivorian cities are poorly documented. This is what justifies this research, the objective of which is to analyze the impact of urban growth on the morphometric configuration of the valleys in the city of Daloa. To achieve this objective, our methodological approach was based on a morphometric analysis of toposequences which consisted mainly of topographic surveys and field observations. The results indicate that in the city of Daloa, the valleys have essentially two types of morphology that depend on the level of densification of housing, economic activities and population density. The valleys with low steepness, gentle slopes and wide bottoms can be seen in the downtown districts; then the moderately steep-sided valleys, with less gentle slopes and relatively narrow bottoms, extend into the districts of the peri-urban belt. In and around the valleys in and around the city centre, population density and construction activities are accelerating diffuse runoff; The wide bottom of the valleys exposes the human and material stakes to the risk of flooding. While, in the valleys of the outlying districts, the more or less steep walls of the slopes accentuate the phenomena of landslides, gullies and landslides of small magnitude.